2018
DOI: 10.2147/oajc.s165827
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous extraction of an embolized progesterone contraceptive implant from the pulmonary artery

Abstract: The Nexplanon® implant is a commonly used radiopaque contraceptive device that contains progestogen associated with an ethylene vinyl-acetate copolymer resulting in a slow release of the active hormonal ingredient. It is inserted into the subdermal connective tissue and provides contraceptive efficacy for up to 3 years. Device removal for clinical, personal or device “end-of-life span” reasons is straightforward. In rare cases, implant migration can occur locally within centimeters of the insertion site. Dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
(33 reference statements)
0
4
0
7
Order By: Relevance
“…El implante anticonceptivo subdérmico de varilla única contiene un progestágeno sintético que proporciona un efecto anticonceptivo por hasta 3 años y tiene el beneficio adicional de ser radioopaco, al contener 15 mg de sulfato de bario, lo que permite su visualización con los métodos de imágenes 1,2 . Es una varilla de 4 cm de longitud y 2 mm de diámetro que se coloca entre 8 y 10 cm por encima del codo, en la cara medial del brazo no dominante [3][4][5][6][7] .…”
Section: Estimados Editoresunclassified
See 1 more Smart Citation
“…El implante anticonceptivo subdérmico de varilla única contiene un progestágeno sintético que proporciona un efecto anticonceptivo por hasta 3 años y tiene el beneficio adicional de ser radioopaco, al contener 15 mg de sulfato de bario, lo que permite su visualización con los métodos de imágenes 1,2 . Es una varilla de 4 cm de longitud y 2 mm de diámetro que se coloca entre 8 y 10 cm por encima del codo, en la cara medial del brazo no dominante [3][4][5][6][7] .…”
Section: Estimados Editoresunclassified
“…En las adolescentes puede generar aumento de peso, acné y cefaleas 3,6,8 . La migración es una complicación poco frecuente, ya sea a sitios cercanos a la inserción o a sitios distantes, incluyendo ramas de la arteria pulmonar 1,2,[5][6][7] .…”
Section: Estimados Editoresunclassified
“…International case reports142–158 describe intravascular migration of 17 ENG-IMP (both Implanon and Nexplanon) to the pulmonary vasculature after presumed insertion into veins in the upper arm. Kang et al 140 reported nine and Ohannessian et al 141 reported seven additional cases of implant migration to the pulmonary vasculature.…”
Section: Complications Of Implant Insertion and Removalmentioning
confidence: 99%
“…If, after appropriate imaging, the ENG-IMP is not identified in the arm, further investigation by specialist services may include serum ENG assay and imaging of the chest – chest X-ray/CT/CT pulmonary angiography according to local protocol 142–157. Case studies report both percutaneous and endovascular retrieval of implants from the pulmonary vasculature as well as implants left in situ 142–157…”
Section: Impalpable and Deeply Sited Etonogestrel Implantsmentioning
confidence: 99%
“…6 Endovascular embolisation of an Implanon NXT device remains a very rare complication in current literature and is limited to case reports. [7][8][9]…”
Section: Answermentioning
confidence: 99%